Ethyl acetate fraction from Cudrania tricuspidata inhibts IL-1β-induced rheumatoid synovial fibroblast proliferation and MMPs, COX-2 and PGE2 production - Eun-Gyeong Lee (Biological Research, 2010)
Objectives: The objective of this study is to determine the effects of Ethyl acetate fraction from Cudrania tricuspidata (EACT) on the interleukin-1b (IL-1b)-induced proliferation of rheumatoid synovial fbroblasts (RASFs) and production of matrix metalloproteinases (MMPs), cyclooxygenase (COX) and prostaglandin E2 (PGE2) by RASFs. Materials and Methods: The proliferation of RASFs was evaluated with CCK-8 reagent in the presence of IL-1b with/without EACT. The expression of MMPs, TIMP-1, COXs, PGE2 and intracellular MAPK signalings, including p-ERK, p-p38, p-JNK and NF-kB were examined by immunoblotting or semi-quantitative reverse transcription-polymerase chain reaction (RT-PCR) and ELISA in conditions as described above. Results: EACT inhibits IL-1β-induced proliferation of RASFs and MMP-1, 3, COX-2 mRNA and protein expression, PGE2 production induced with IL-1b. EACT also inhibits the phosphorylation of ERK-1/2, p38, JNK and activation of NF-kB by IL-1b. Conclusions: These results suggest that EACT might be involved in synovial fbroblast proliferation and MMPs, COX-2, and PGE2 production, which are involved in joint destruction in rheumatoid arthritis (RA), indicating that this might be a new therapeutic modality for management of rheumatoid arthritis.